Prevalencia de Helmintos Enteroparásitos Zoonóticos y Factores Asociados en (canis familiaris) en el Barrio Chinchil Robayos, Chinchil Villamarin, Trompucho. - Amaguaña Guanopatin, María José (2019)
In the present project, the prevalence of enter parasitic helminths and associated factors (Canis familiaris) was determined through the coproparasitic examination and the clinical record for compliance with prevention measures in Chinchil Robayos, Chinchil Villamarin, Trompucho neighborhoods. An exploratory study was carried out, collecting samples of 75 canines that included the ages of 0-12 months, 1-5 years and> of 5 years of three rural neighborhoods; The samples are processed by the "Faust Technique" for the identification of the parasites. The results indicated that the canines presented 100% of parasitosis at different ages, 23% of Ancylostoma caninum, Toxocara canis 23%, Dipylidium caninum 31%, Strongylus 22%. The associated factors and parasitosis are related to the zoonotic distribution, because there is no sanitary control on the part of the owners that mainly affect the health of the dogs. The study of the factors is related to the accounts where the prevalence of parasitic is shown is associated with 87% of canines. % do not have a deworming calendar and 85% have little or no veterinary control. Owners were informed that the results of coproparasitic exams, parasites, children, children, children, children, children, children.